Stability of lenalidomide suspension after preparation by a simple suspension method for enteral tube administration. (August 2016) - Morita, Tomoko O; Yamaguchi, Ayumi; Kimura, Sadaaki; Fujii, Hirofumi; Endo, Kazushi; Izumi, Keishiro; Saito, Shinichiro; Minami, Hironobu
Purpose: A simple suspension method has been developed for tube administration, in which tablets (and capsules) are disintegrated in hot water (55℃) without grinding (or opening) them. In the present study, we evaluated the feasibility of this simple suspension method for the preparation of lenalidomide (Celgene, Summit, New Jersey and USA) suspension by testing the stability of this drug at 55℃ and its adsorbability on the tube. Methods: We examined, by high-performance liquid chromatography, the time-dependent changes in the concentration of lenalidomide in suspensions of the drug prepared by the simple suspension method. The high-performance liquid chromatography analyses of lenalidomide were performed on Prominence LC-20AB/SPD-20 A (Shimadzu, Kyoto, Japan) with a ZORBAX SB-C18 RR analytical column (Agilent Technologies, Santa Clara, California, USA; particle size: 2.1 × 100 mm, 3.5 µm) at a flow rate of 0.4 mL/min. A solvent system consisting of 10 mM ammonium acetate (pH 7.0)/acetonitrile was used as the eluent and the eluate was detected by UV at 254 nm. Results: Lenalidomide was confirmed to remain stable in hot water at 55℃ for 24 h in the prepared suspension by the simple suspension method, and more than 99% of the drug could be recovered from the suspension. In addition, 94.5–98.0% of the drug amount could pass through a percutaneous endoscopic gastrostomy tube. Lenalidomide was scarcely adsorbed on to the percutaneous endoscopic gastrostomy tube made of polyurethane or polyvinyl chloride. Conclusion: Lenalidomide was found to be stable even in hot water and was not adsorbed on to the percutaneous endoscopic gastrostomy tube.